Isolation and Identification of Pathogenic Bacteria Associated with Tomatoes, Bananas, Spinach and Okra commonly sold at Old Market, Patigi, Kwara State, Nigeria - F. B. Abdulrahaman; J. Mohammed; T. Z. Abdulkareem (Journal of Applied Sciences and Environmental Management)
Fresh fruits and vegetables are vital components of a healthy diet but are often linked to foodborne illnesses due to microbial contamination. Thus, the objective of this paper is to isolate and identify pathogenic bacteria associated with Tomatoes (Solanum lycopersicum), bananas (Musa spp.), spinach (Spinacia oleracea), and okra (Abelmoschus esculentus) commonly sold at Old Market, Patigi, Kwarra State, Nigeria using standard microbiological techniques. Bacterial load of fresh produce range from 0.7 x - 1.8 x and from 3.3 x -7.0 x in spoiled produce.The total bacterial load was higher in spoiled produce, with spoiled bananas recording 7.0 × 10⁴ cfu/ml, while fresh okra had the lowest bacterial load of 0.7 × 10⁴ cfu/ml. Morphological and biochemical analyses identified Escherichia coli, Salmonella spp., Klebsiella pneumoniae, Staphylococcus aureus, Pseudomonas aeruginosa, Bacillus subtilis, and Enterobacter aerogenes. Klebsiella pneumoniae was the most prevalent species, occurring in 66.67% of banana samples, 33.33% of spinach samples, and 33.33% of tomato samples. These findings highlight significant microbial contamination of fresh and spoiled produce, emphasizing the potential health risks associated with consuming raw or minimally processed fruits and vegetables. The study underscores the need for improved hygiene practices during handling, storage, and sale, as well as the implementation of regular microbiological monitoring to ensure food safety in local markets.